Eroticism—Politics—Identity: The Case of Richard III - Kizelbach, Urszula (Text Matters: A Journal of Literature, Theory and Culture, 2013)
Richard III’s courtship of Lady Anne in William Shakespeare’s King Richard III is a blend of courtly speech and sexual extravaganza. His sexual energy and power of seduction were invented by Shakespeare to enhance the theatrical effect of this figure and, at the same time, to present Richard as a tragic character. Richard’s eroticism in Act 1 Scene 2 makes him a complicated individual. Playing a seducer is one of the guises he uses to achieve his political aims on the one hand, and, on the other, the pose of a sexually attractive lover enables him to put his masculinity to the test. Throughout the scene Richard is haunted by his deformity that, together with his villainy, makes him a stranger to the world and an enemy to his family and the court. In order to overcome his self-image of a disproportional cripple he manifests his sexuality towards Anne to boost his self-esteem and to confirm that the lady will accept him despite his obvious physical shortcomings. This article uses Georges Bataille’s theory of eroticism and erotic desire to characterize Richard as a tragic individual and to explain the reasons behind his unexpected sexual behaviour in the seduction scene.